PANGGILAN UNTUK MEMUJI TUHAN BERDASARKAN MAZMUR 103 DAN IMPLIKASINYA BAGI ORANG PERCAYA MASA KINI - Lawrence Christian (The Way Jurnal Teologi dan Kependidikan, 2020)
Many people when they have problems only focus on the problem and cannot feel God's goodness. No matter how hard the problem, you can still feel God's goodness. May this kindness be a reason to praise God when experiencing problems. The research objective is to find reasons for praising God according to Psalm 103. This research uses descriptive-inductive methods. The result of this research is the nature of Allah who is gracious and compassionate, long patient and also a lot of kindness. Researchers conclude that whatever happens in the life of a believer he must still praise God.